Analysis of the Effect of Poverty Level, Unemployment and Economic Growth on the Human Development Index in West Nusa Tenggara Province in 2017-2022 - Fitratul Nakyah; Muhammad Alwi; Endang Astuti (Economy and Finance Enthusiastic, 2024)
This research aims to analyze the influence of poverty levels, unemployment and economic growth on the human development index in Nusa Tenggara Barat province in 2017-2022. The type of research used is quantitative research. The data used comes from the Central Statistics Agency of Nusa Tenggara Barat Province, totaling 10 Regencies/Cities. The data was processed using the Eviws 10 application with the panel data regression analysis method with the Fixed Effect Model approach. The results of this study show that partially the value of prob. The poverty level variable of 0.00 is smaller than the significance level (α) of 0.05, which means that the poverty level has a negative and significant effect on the human development index, while the prob. The unemployment variable of 0.84 is greater than the significance level (α) of 0.05, which means that unemployment has a negative but not significant effect and the prob. The economic growth variable of 0.20 is greater than the significance level (α) of 0.05, which means that economic growth has a positive but not significant effect on the human development index in Nusa Tenggara Barat Province. Meanwhile, the results of simultaneous testing (F test) of the three variables of poverty, unemployment and economic growth have a joint effect on the human development index. The implications of this research can be a guide for policy makers in efforts to improve human development in Nusa Tenggara Barat Province.